Validation of the Malay Version of Short Informant Questionnaire on Cognitive Decline in the Elderly (MS-IQCODE) - Othman, Zahiruddin; Siong, Teck Wong; Drahman, Ismail; Kok, Wei Wee (Japan International Cultural Exchange Foundation, 2015)
Aims: The short Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) is a self-administered informant- based report on cognitive decline. The aim of this study was to translate and validate the short IQCODE into Malay for more widespread use in clinical practice. Methods: The short IQCODE was translated into Malay language using forward and back translation method. The face and content validity was acceptable. The final Malay version was administered to 50 caregivers of post-stroke patients attending the medical clinic of Hospital Umum Sarawak in December 2011. Results: The Malay version of short IQCODE (MS-IQCODE) has a good face and content validity. It also displayed good internal consistency with Cronbach's alpha 0.94. Conclusions: The MS-IQCODE is a reliable tool for the assessment of cognitive decline in the elderly in Malaysian population.